Policy on Maritime Border Disputes Between Indonesia and Australia: Stephen M. Walt’s Neorealism Perspective - Nadia Saidah Rahayu; Najma Imtinan Rasaf; Ghana Aldila Septiani; Penny Respati Yurisa (Prodi Hubungan Internasional Program Magister Univ. Muhammadiyah Yogyakarta, 2023)
Indonesia is a maritime country with an Exclusive Economic Zone (EEZ) covering an area of 7.81 million square kilometers. Consequently, Indonesia has numerous disputes with neighboring countries regarding maritime boundaries in the EEZ, particularly with Australia. Several incidents have strained the relationship between the two countries. For example, from December 2013 to January 2014, there were six instances of the Australian Navy unintentionally violating Indonesian waters during border operations. Other issues include illegal fishing, human trafficking, illegal transshipment, and, more recently, an Australian warship's breach of Indonesian waters on September 8, 2022. Maritime boundary disputes occur when two or more countries have overlapping claims in the same maritime territory. These disputes can be caused by differences in the interpretation of international law, conflicting economic interests, historical or cultural claims, or geopolitical tensions between the involved nations. Maritime boundary disputes can be resolved through negotiations, international arbitration, mediation, or legal processes. In this case, the neorealism theory, developed by Stephen M. Walt, provides an understanding of international relations, changes in power structures, conflicts, cooperation among nations, and the factors influencing foreign policies. By applying Stephen M. Walt's neorealism theory, this study analyzes the policy frameworks of Indonesia and Australia in managing their international relations and the factors that have led to the disputes between the two.